Adjunctive Effects of Bajakah Wood (Spatholobus littoralis Hassk.) on Cholesterol and Triglyceride in EGFR Wild Type Lung Adenocarcinoma Patients - Nikmah, Elok Hikmatun; Kusumawardhani, Erna; Suhartono, Eko; Nurrasyidah, Ira; Ansori, Isa; Assagaf, Ali; Isa, Mohamad; Haryati, Haryati; Oktaviyanti, Ika Kustiyah (Faculty of Medicine Universitas Airlangga, 2026)
Introduction: Lung cancer is the leading cause of cancer mortality, influenced by uncontrolled cell proliferation, migration, metastasis, and mutations. The imbalance of high-density lipoprotein (HDL) and triglycerides (TG) has an important role. Spatholobus littoralis Hassk., or Bajakah wood, has antioxidant effects due to dihydrokaempferol, which lowers cholesterol levels and increases HDL. This additional therapy is expected to have a positive impact, supporting treatment for patients with wild-type lung adenocarcinoma. Methods: This was a single-blind clinical trial conducted at Ulin General Hospital, Banjarmasin, Indonesia, in patients with epidermal growth factor receptor (EGFR)-wild-type lung adenocarcinoma at a minimum stage IIIA, from June 2023 to July 2024. The participants were divided into two groups: the treatment group (adjunctive Bajakah wood 1,000 mg) and the control group. Cholesterol, low-density lipoprotein (LDL), HDL, and TG were measured twice before starting chemotherapy and after the third chemotherapy cycle. The resulting data were analyzed using the independent t-test and the Mann-Whitney test through the Statistical Package for the Social Sciences (SPSS) version 26. Results: For the 21 total patients, the cholesterol and TG levels in the treatment group before and after the third chemotherapy were 200.55±42.65 to 184.45±24.20 and 131.27±44.76 to 112.73±34.74, respectively. The control group results were 185.10±51.98 to 168.30±32.89 and 118.30±51.30 to 104.10±12.53, respectively. The comparison of changes between the two groups was not significant (p-value > 0.005). Conclusion: Cholesterol and TG levels were reduced, but there were no statistically significant differences after the addition of therapy with Bajakah wood.